TRENDS IN INCIDENCE OF POVERTY AMONG SCHEDULED CASTES: THE CASE OF KARNATAKA - Naz, Sumayya; Vishwanatha (International Journal of Research -GRANTHAALAYAH, 2019)
Historically, the Scheduled Castes (SCs) in India have been the victims of social exclusion and marginalization along with living under poverty. The SCs in Karnataka form a sizeble part with 17 per cent of the State’s population and more than 75 per cent of them living in rural areas. They have continued to be socially, educationally and economically backward even today. Due to various constitutional provisions and welfare programmes for SCs, the incidence of poverty is declining in percentage terms but a large number of SC population still continue to be poor. A large number of studies have focused on the issue of poverty in general, but not many studies relating to incidence of poverty across social groups in India and Karnataka. In this backdrop, the present paper is to analyse the trends in prevalence of poverty among SCs in Karnataka at macto perspective.